PERANCANGAN SISTEM INFORMASI E-COMMERCE BERBASIS PROTOTYPE PADA TOKO SEHATI - Lailatul Akmal; Tata Sutabri (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Information technology is very influential for the progress of a business. Especially in this day and age, there are various ways to promote your business, one of which is by using an e-commerce website. E-commerce is a buying and selling activity carried out online through a site or website. In the SEHATI Shop research, the problems that are often encountered are promotional media only using banners, banners, promotional sheets, sales are still limited to offline/not yet reaching a wide market, data storage and printing reports are still in the form of recording in the form of manual archives. The purpose of this research is to provide solutions to existing problems by designing an e-commerce-based sales information system. The results and conclusions of this study are that e-commerce-based sales websites can be used as promotional media, simplify the sales process that is carried out online, and can facilitate data processing and printing reports that no longer require recording in the form of manual archives.